1999
DOI: 10.1080/17450399909386167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to dietary nivalenol on activity of enzymes involved in glutamine catabolism in the epithelium along the gastrointestinal tract of growing pigs

Abstract: Changes in the activity of enzymes involved in oxidative metabolism of glutamine, and in protein content, in the epithelial tissue along the gastrointestinal (GI) tract of growing pigs exposed to nivalenol (NIV) in the diet were investigated. The epithelial tissue was taken from the stomach, small intestine and colon of three groups of animals fed diets without NIV (control), with inclusion of 2.5 mg NIV/kg diet (low dose) and with inclusion of 5.0 mg NIV/kg diet (high dose). The activities of glutaminase, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Trenholm et al (1989) reported that pigs are the most sensitive farm animals to tricothecenes, with exposure associated with reduced feed intake and liveweight gain. In another study, a statistically significant decrease in the activity of oxoglutarate dehydrogenase was reported in small intestine and colon epithelium of 51 day-old male pigs (Landrace x Yorkshire) administered with a diet containing 2.5 or 5 mg nivalenol/kg for three weeks (Madej et al, 1999). The exposure to nivalenol via the feed, estimated to be 0.1 or 0.2 mg nivalenol/kg b.w.…”
Section: Ruminantsmentioning
confidence: 94%
“…Trenholm et al (1989) reported that pigs are the most sensitive farm animals to tricothecenes, with exposure associated with reduced feed intake and liveweight gain. In another study, a statistically significant decrease in the activity of oxoglutarate dehydrogenase was reported in small intestine and colon epithelium of 51 day-old male pigs (Landrace x Yorkshire) administered with a diet containing 2.5 or 5 mg nivalenol/kg for three weeks (Madej et al, 1999). The exposure to nivalenol via the feed, estimated to be 0.1 or 0.2 mg nivalenol/kg b.w.…”
Section: Ruminantsmentioning
confidence: 94%
“…The homogenate was used as the GA enzyme solution. GA activity was measured based on the methods of Madej et al . (1999), and the reaction product Glu was assayed at 340 nm, in accordance with the methods of Bernt and Bergmeyer (1974).…”
Section: Methodsmentioning
confidence: 99%
“…The GDH enzyme solution was prepared according to the methods of Madej et al (1999). The frozen muscle was homogenized in homogenate buffer (50 mmol/L triethanolamine/Cl, 1 mmol/L ethylenediaminetetraacetic acid (EDTA), 2 mmol/L magnesium chloride and 26 mmol/L mercaptoethanol, pH 7.5) using a high-speed homogenizer (Ultra-turrax T25 basic; Ikawerke, Staufen, Germany).…”
Section: Measurement Of Enzyme Activitiesmentioning
confidence: 99%
“…GA activity was measured with the methods of Madej et al (1999), and measurement of the reaction product Glu was carried out following the methods of Bernt and Bergmeyer (1974). GS activity was measured with the methods of Arola et al (1981).…”
Section: Measurements Of Enzyme Activitiesmentioning
confidence: 99%
“…GDH solution was prepared using the methods of Madej et al (1999). The frozen muscle (0Á5 g) was homogenised on ice in 10 ml buffer (50 mM triethanolamine/Cl, 1 mM EDTA, 2 mM magnesium chloride and 26 mM mercaptoethanol, pH 7Á5) using a high-speed homogeniser (Ultraturrax T25 basic, IKA-WERKE).…”
Section: Preparation Of Enzyme Solutionmentioning
confidence: 99%